Strategi Kepala Sekolah Dalam Mendukung Pembinaan Guru - Sabariah Sabariah; Khalisyah Listiani; Atiqoh Atiqoh; Wawan Gunawan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Teacher development is crucial as it helps teachers enhance their competence, the quality of teaching, student achievement, and school performance. This research aims to explain the strategies of school principals in supporting teacher development. The research was conducted qualitatively at Banua Hanyar Public Elementary School, Telaga Langsat Subdistrict, South Hulu Sungai Regency, Banjarmasin. Data were collected through interviews, observations, and documentation. Data were processed through data reduction, data presentation, and drawing conclusions. The results show that to improve teacher development in the school, the principal employs several methods: firstly, assigning additional tasks to teachers, including tasks such as supervisor, student self-development coordinator, Pancasila profile strengthening coordinator, school treasurer, school health unit coordinator, religious program coordinator, school exam coordinator, education administration coordinator, and arts coordinator at the school. Secondly, empowering school resources by enhancing teacher quality through training, improving learning facilities by providing laptops, LCD projectors, and wifi, as well as utilizing information technology through learning platforms. Conclusion: the strategies implemented by the principal have been maximized to support teacher development. Research contribution: serving as a reference for other schools to develop teachers to become more professional.